8‐Hydroxyquinoline Functionalized PEG‐1000 Bridged Dicationic Ionic Liquid as a Novel Ligand for Copper‐catalyzed N‐Arylation of Imidazoles. Issue 8 (10th May 2013) - Wang, Ying‐Lei; Luo, Jun; Liu, Zu‐Liang
Abstract A novel 8‐hydroxyquinoline functionalized PEG‐1000 bridged dicationic ionic liquid ([HQ‐PEG1000‐DIL][BF4]) was synthesized and characterized. It was applied as an efficiently recyclable ligand for copper‐catalyzed N‐arylation of nitrogen‐containing heterocycles with aryl halides. The catalytic system could be easily recovered and reused for at least five runs without obvious loss of catalytic activity.